Metastasis: A Bane of Breast Cancer Therapy - Chidalu A. Edechi, (European Medical Journal, 2020)
The underlying mechanisms of metastasis in patients with breast cancer is still poorly understood. Approximately 6% of patients with breast cancer present with metastasis at the time of diagnosis. Metastatic breast cancer is difficult to treat and patients with breast cancer with distant metastasis have a significantly lower 5-year survival rate compared to patients with localised breast cancer (27% and 99%, respectively). During breast cancer progression, tumour cells first metastasise to nearby draining lymph nodes and then to distant organs, primarily bone, lungs, liver, and brain. In this brief review, the authors discuss breast cancer metastasis, the role of epithelial–mesenchymal transition and the contributions of the immune system to the metastatic process. The authors also briefly discuss whether there is any relationship between tumour size and metastatic potential, and recent advances in treatment for metastatic breast cancer. The studies highlighted suggest that immunotherapy may play a more significant role in future patient care for metastatic breast cancer.